Different incidence of interstitial lung disease according to different kinds of EGFR‐tyrosine kinase inhibitors administered immediately before and/or after anti‐PD‐1 antibodies in lung cancer. Issue 4 (12th March 2019) - Uchida, Takahiro; Kaira, Kyoichi; Yamaguchi, Ou; Mouri, Atsuto; Shiono, Ayako; Miura, Yu; Hashimoto, Kosuke; Nishihara, Fuyumi; Murayama, Yoshitake; Kobayashi, Kunihiko; Kagamu, Hiroshi
Abstract : Background: The aim of our study was to retrospectively assess the incidence of interstitial lung disease (ILD) related to EGFR‐tyrosine kinase inhibitor (TKI) treatment immediately before and/or after the administration of a PD‐1 antibody. Methods: We analyzed the data of 26 patients who underwent treatment with EGFR‐TKIs immediately before and/or after the administration of an anti‐PD‐1 antibody. Results: Four out of the 26 patients developed ILD during EGFR‐TKI treatment: three patients during the administration of osimertinib immediately after, and one during afatinib immediately before treatment with an anti‐PD‐1 antibody. Three of 12 patients who underwent EGFR‐TKI therapy immediately after anti‐PD‐1 antibody treatment experienced osimertinib‐induced ILD. ILD was not observed in the five patients administered an anti‐PD‐1 antibody followed by first or second‐generation EGFR‐TKIs. Conclusion: ILD was observed in the treatment sequence of an anti‐PD‐1 antibody followed by osimertinib, but not with first or second‐generation EGFR‐TKIs.